White Emotion and White Scopophilia: The Myth of Docile and Brute Blacks - Sayyed Navid Etedali Rezapoorian (American and British Studies Annual)
This article investigates the resilience of the docility and brutality myths attributed to African Americans as demonstrated by three fairly recent film renditions. The focus is on the historical origins and the continued relevance of these tropes through white scopophilia and cognitive dissonance. The myths are analyzed in terms of their role in justifying racial hierarchies and reinforcing white supremacy within historical and contemporary contexts. Through a critical examination of historical texts by Lerone Bennett Jr. and portrayals in films such as Django Unchained and Twelve Years a Slave, the study demonstrates how these stereotypes are alternately emphasized or diminished to maintain white dominance. It argues that white America constructs African American identities with a strategic oscillation between docility and brutality to sustain control and alleviate white guilt. This manipulation is facilitated by psychological mechanisms that allow white individuals to hold contradictory beliefs about race without recognizing their inconsistencies. By detailing the dynamic usage of these myths, the article highlights how they are not static, but are strategically deployed to reaffirm white moral and authoritative supremacy as needed. The conclusion calls for a critical reassessment of racial representations in media and historical narratives to disrupt these enduring racial myths.